RESPONS PERTUMBUHAN KEDELAI TERHADAP PEMANGKASAN DAN PEMBERIAN KOMPOS TKKS PADA LAHAN TERNAUNGI - Suci Islami Pane; Lisa Mawarni; T Irmansyah (Universitas Sumatera Utara, 2013)
Response growth of soybean by cutting and giving empty fruit bunches of oil palm compost inshaded area.Using of shaded area for soybean plantation faced trouble such yield decreasing.For that purpose cutting and giving empty fruit bunches of oil palm (EFBOP) compost aimed toincrease growth of soybean in shaded area. This research was conducted at experimental field ofFakultas Pertanian USU in January-April 2013 using factorial randomized block design with twofactor, i.e. time of cutting (no cutting, cutting in V5, cutting in R1) and dose of EFBOP compost(0, 10, 20 and 30 ton per ha). Parameter observed were plant height, summarize of leaf area, stemdiameter, and shoot root ratio. The result showed that cutting significantly decreased plant heightbut increase all parameter observed. Dose of EFBOP compost significantly increased summarize ofleaf area and stem diameter. The interaction of two factor significantly increased summarize of leafarea. The best result were showed by cutting in V5 and giving 30 ton per ha EFBOP compost.Keywords : cutting, EFBOP compost, shaded area, soybean.